Analisis Pengaruh Promosi Daya Tarik Dan Lokasi Terhadap Keputusan Pengunjung Di Tempat Wisata Tradisonal Takpala Desa Lembur Barat Kecamatan Alor Tenga Utara Kabupaten Alor Tahun 2022-2023 - Maukari, Lodia Maukari; Anigomang, Ferdinand Romelus; Maruli, Elia; Awang, Mesak Y. (Jurnal Ilmiah Wahana Pendidikan, 2023)
Lodia Maukari, Thesis Title: Analysis of the influence of promotion, attractiveness, and location on visitor decisions at Takpala Traditional Tourist Sites, West Overtime Village, Alor Tenga Utara District, Alor Regency in 2021-2022. Supervisior 1 Mr. Elia Maruli, SE. MM and supervisior II Mrs. Yustina Maro, SE. MM. This study aims to determine the effect of promotion of attractiveness, and location on visitor decisions at Takpala Traditional Tourist Attractions, Lembur Baraf Village, Alor Tenga Utara District, Alor Regenci in 2021-2022. The sample from this research is 40 consumers. Data collection using observation techniques, interviews, questionnaires. Data was then analyzed using multiple linear regression analysis to find out the independent variable on (X) on the denpendent variable (Y). The results of this study showed that the promotion variable (X1) and local variable (x2) and local variable (X3) had a significant effect on decision visitors (Y) at Takpala Traditional Tourism Place, West Overtime Village, Alor Tenga Utara District, Alor Regency in 2021-2022, while the attractiveness variable (X2) has no effect on visior decision variables (Y) at Takpala Trditional Tourism Sites, West Overtime Village, Alos Tenga Utara District Alor Regenciy Year 2021-2022. Based on the result of the research, it is suggested that the head of sangus. Provide more promotion, cleanliness for attractiveness and location determination, so that automatically visitor’ decision at the Takpala Traditional Toursit Site increase.